Desenvolvimento e caracterização de sistema nanoestruturado contendo miconazol e farnesol para o tratamento de candidíase vulvovaginal - Costa, Adelaide Fernandes (2016)
Vulvovaginal candidiasis (VVC) is caused mainly by opportunistic fungus Candida albicans and its yeast to hyphae transition is considered the major virulence factor of this pathogen. The increased incidence of VVC has highlighted the importance of developing new therapeutic strategies. The objective of this study was to develop a mucoadhesive nanostructured system comprising miconazole, and farnesol within chitosan for the treatment of VVC. The drug showed the antifungal miconazole expected efficacy with minimal inhibitory concentration (MIC) of 1 μg/mL. The farnesol quorum-sensing molecule was capable of inhibiting hypha-transition yeast at levels greater or equal to 300 μM. When tested together, farnesol has no effect compared to the MIC obtained for miconazole. Nanoparticles of chitosan-containing miconazole and farnesol were prepared by ionic gelation and showed favorable characteristics for use on mucous membranes, such as diameter less than 300 nanometers (nm), polydispersion index (PDI) less than 0.3, positive zeta potential and acid pH. The encapsulation efficiency (EE) of the nanoparticles was on average 81.1% for miconazole, 31.9% farnesol and 32.7% and 70.0% for miconazole and farnesol when co-encapsulated, respectively. The nanoparticles showed instability as the diameter and PDI, but were stable compared to the EE. Regarding toxicity in cultured fibroblasts (Balb/ c 3T3) were considered non-toxic. The nanoparticles showed antifungal activity against C. albicans strain used, with MIC of 2.5 μg/mL and 2 μg/mL for nanoparticles with miconazole and miconazole/ farnesol, respectively. Nanoparticles containing farnesol inhibit yeast-hyphae transition at concentrations greater than or equal to 240 uM. The antifungal activity in vivo was assessed in the murine model for VVC. Although there is no statistically significant difference between treatments in relation to the counting of colony forming units (CFU), the results suggest that chitosan nanoparticles containing miconazole and farnesol were effective for inhibiting fungal proliferation and chitosan nanoparticles containing farnesol were capable of decreasing the pathogenicity of infection demonstrated by the absence of inflammation.